Novel Camel (Camelus Dromedaries) Urine Peptides with Dual Antibacterial And Anticancer Activity - Eman Mohammed Halawani (International Journal of Pharma and Bio Sciences, 2021)
Antimicrobial peptides are important naturally occurring molecules with broad activity against pathogenic microbes and even cancer cells. The present study aims to discover new natural peptides derived from camel excretion and their biological effects on harmful bacteria and cancer cells. Camel antimicrobial peptides were separated from total protein by acrylamide gel electrophoresis. Then, the antibacterial and anticancer activities of camel urine peptides were investigated to determine their activity against resistant bacterial cells as well as human liver, colon, and breast carcinoma cell lines. The major detected urine peptides had molecular weights of 12.9 and 16.6 kDa, and they were relatively stable to heat and proteolytic enzymes. They exhibited lethal antibacterial activity against multidrug-resistant, Gram-positive, methicillin-resistant Staphylococcus aureus and multidrug-resistant, Gram-negative Salmonella typhimurium DT104 within 2 to 4 hours. The peptides also demonstrated dose-dependent cytotoxicity at 18.1, 35.2, and 40.4 µg/ml against HCT116 colon carcinoma, HEPG-2 human liver carcinoma, and MCF-7 breast cancer cell lines, respectively. These unique peptides, which are part of the innate immunity of camel urine, are primary candidates for use as natural remedies against cancer and bacterial infections.